2022
DOI: 10.1186/s40360-022-00593-3
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol’s neural protective effects for the injured embryoid body and cerebral organoid

Abstract: Objective Resveratrol (RSV) is a polyphenol compound found in grapes, veratrum and other plants. It has been reported that RSV has anti-inflammatory, anti-oxidant, anti-cancer and other pharmacological effects. However, the impacts of RSV on development of nervous system are not understood well. The study aims to investigate RSV’s neuroprotective effect during development and to provide a health care for pregnant women and their fetuses with RSV supplementation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Wang et al have evaluated the neuroprotective mechanism of resveratrol using cerebral organoids 3D-cell culture. The result showed that resveratrol could protect the neuronal cell from damage caused by D-galactose by inducing neuronal cell proliferation, inhibiting apoptosis, and enhancing the differentiation of germ layers [57]. These results show the initial applications and potential of using 3D-cell culture models in the study of toxicity and bioactivity of nutraceutical compounds.…”
Section: D-cell Culturementioning
confidence: 70%
“…Wang et al have evaluated the neuroprotective mechanism of resveratrol using cerebral organoids 3D-cell culture. The result showed that resveratrol could protect the neuronal cell from damage caused by D-galactose by inducing neuronal cell proliferation, inhibiting apoptosis, and enhancing the differentiation of germ layers [57]. These results show the initial applications and potential of using 3D-cell culture models in the study of toxicity and bioactivity of nutraceutical compounds.…”
Section: D-cell Culturementioning
confidence: 70%
“…In addition to using patient-derived cerebral organoids, we could also treat cerebral organoids with certain drugs in vitro to mimic aging or damaged brains in humans. These induced disease models include the D-galactose-induced aging model [ 6 ], the hydrogen peroxide-induced oxidative stress model [ 7 ], the lipopolysaccharide (LPS)-induced inflammation model [ 8 ], the alcohol-induced neurotoxicity model [ 9 , 10 ], etc. These organoid models have contributed to our understanding of disease mechanisms and driven innovation for new therapies.…”
Section: Introductionmentioning
confidence: 99%